Hormonal regulation of crop architecture in response to strong soil - Lloyd, David Paul Alex (2016)
The architecture of crop plants is determined by adaptation to environmental conditions within genetic constraints and has considerable influence on the ability of a crop to produce high yields. The abiotic stress of strong soil reduces growth of roots and shoots, limiting the yields of wheat and rice plants. This project investigates the hormonal signals mediating architectural responses to strong soil, aiming to improve the understanding of this plant-environment interaction. Strigolactones are plant hormones known to inhibit shoot branching (tillering in grasses) in a range of plant species. This project demonstrates that strigolactones are, at least in part, responsible for mediating the reduction in tillering in rice plants in response to strong soil. This is demonstrated by a diminished tillering response to strong soil in rice mutants defective in biosynthesis or perception of strigolactones. Additionally, roots of rice plants grown in strong soil contained higher levels of endogenous strigolactone than roots of rice plants grown in weak soil. The identification of wheat orthologues of strigolactone biosynthesis genes is conducted and transgenic lines with reduced expression of these genes are produced, enabling the dissection of the role of strigolactones in wheat in response to strong soil to be explored. Gibberellin is known to be responsible for promoting leaf elongation in plants. This project demonstrates that gibberellin is responsible for the reductions in leaf elongation in wheat in response to strong soil. Increased levels of bioactive gibberellin are shown to be required for the response to occur and exogenous application of bioactive gibberellin is shown to recover leaf elongation in strong soil conditions. Finally, this project implicates a number of other hormones as being involved in responding to strong soil in wheat through global hormone profiling.